Adult sex ratios and reproductive strategies: a critical re-examination of sex differences in human and animal societies. (19th September 2017) - Schacht, Ryan; Kramer, Karen L.; Székely, Tamás; Kappeler, Peter M.
Abstract : It is increasingly recognized that the relative proportion of potential mates to competitors in a population impacts a range of sex-specific behaviours and in particular mating and reproduction. However, while the adult sex ratio (ASR) has long been recognized as an important link between demography and behaviour, this relationship remains understudied. Here, we introduce the first inter-disciplinary collection of research on the causes and consequences of variation in the ASR in human and animal societies. This important topic is relevant to a wide audience of both social and biological scientists due to the central role that the relative number of males to females in a population plays for the evolution of, and contemporary variation in, sex roles across groups, species and higher taxa. The articles in this theme issue cover research on ASR across a variety of taxa and topics. They offer critical re-evaluations of theoretical foundations within both evolutionary and non-evolutionary fields, and propose innovative methodological approaches, present new empirical examples of behavioural consequences of ASR variation and reveal that the ASR plays a major role in determining population viability, especially in small populations and species with labile sex determination. This introductory paper puts the contributions of the theme issue into a broader context, identifies general trends across the literature and formulates directions for future research. This article is part of the themed issue 'Adult sex ratios and reproductive decisions: a critical re-examination of sex differences in human and animal societies'.